Pengaruh Model Pembelajaran Kontekstual terhadap Minat Belajar Pendidikan Agama Kristen dan Budi Pekerti Siswa Kelas X SMK Negeri 1 Siborongborong Tahun Pembelajaran 2023/2024 - Yuli Arta Simbolon; Dame Taruli; Regina Nainggolan; Maria Widiastuti; Raikhapoor Raikhapoor (Coram Mundo: Jurnal Teologi dan Pendidikan Agama Kristen, 2024)
The purpose of this research is to determine the influence of the contextual learning model on interest in learning Christian Religious Education and Characteristics of class X students at SMK Negeri 1 Siborongborong for the 2023/2024 academic year. The research method used is a quantitative method with a descriptive inferential type. The population is all 334 students of class Data was collected using a closed questionnaire with 20 items for variable Interest in studying Christian Religious Education and Character Education for class X students at SMK Negeri 1 Siborongborong for the 2023/2024 Academic Year. Influence test: a) regression equation test obtained regression equation Ŷ=18.83+0.753 X. b) regression coefficient of determination test (r2) = 63.3%. c) hypothesis testing using the F test obtained Fcount = 8.313 > Ftable = 1.86. Thus Ha, that is, there is a positive and significant influence of the contextual learning model on interest in learning Christian Religious Education and Characteristics of class X students at SMK Negeri 1 Siborongborong for the 2023/2024 academic year accepted and H0 rejected.